PENDIDIKAN ISLAM DALAM PERSPEKTIF HADIS - Munirah Munirah (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2016)
The importance of education has been emphasized repeatedly in the Qur’an and hadith. The hadith of the Prophet Muhammad also emphasise the value of knowledge. In the Qur’an and hadith, the importance of education is explicit; in Islam seeking education is obligatory, and that knowledge is considered to be the path towards greater closeness to Allah. In the hadith term of education or tarbiyah can be found as Ta'līm, from the root 'alima (to know, to be aware, to perceive, to learn), Tarbiyah, from the root raba (to increase, to grow, to rear), Ta'dīb, from the root addaba (to be cultured, refined, well-mannered). The hadith also affirms that there are two important elements that are necessary ingredients in the formulation of a philosophy of Islamic education namely, the goal of education and educational factors.